Exploration of gender sensitivity competence of guidance and counseling teachers in handling victims of sexual harassment in schools - Bulantika, Siti Zahra; Sari, Rizka Puspita; Irawan, Andi Wahyu (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to explore the gender sensitivity competence of Guidance and Counseling (BK) teachers in handling cases of sexual harassment in schools in Lampung. The research employed a qualitative approach with a phenomenological design. Data were collected through semi-structured interviews with five BK teachers who had experience in handling sexual harassment cases. The findings revealed that participants' understanding of gender issues and sexual harassment was still limited. Participants tended to view sexual harassment as a problem that occurs more frequently among female students, often overlooking the fact that male students are also vulnerable to becoming victims. This reflects a limited understanding of sexual harassment and gender issues. In terms of skills, the study found that participants had not fully mastered gender-sensitive counseling skills. For instance, some participants tended to blame the victim based on appearance or behavior, indicating a lack of ability to provide empathetic and unbiased support. Furthermore, the attitudes of BK teachers toward sexual harassment cases were still influenced by gender stereotypes. This study highlights the importance of ongoing training to enhance the gender sensitivity competence of BK teachers, enabling them to offer more empathetic and inclusive support to all victims of sexual harassment in the school environment.